Age-Adjusted D-Dimer in Ruling Out Acute Aortic Syndrome - Dayeon Lee; Yong Won Kim; Tae Youn Kim; Sanghun Lee; Han Ho Do; Jun Seok Seo; Jeong Hun Lee (Emergency Medicine International)
Background. Recently, D-dimer has been suggested as a biomarker to rule out acute aortic syndrome (AAS). Since it increases with age, this study was conducted to reveal whether an age-adjusted D-dimer can increase diagnostic accuracy in ruling out AAS. Method. A retrospective observational study design was used. Consecutive adult patients who visited an emergency room between January 2015 and September 2020 and who underwent a D-dimer test and computed tomography angiography for suspected AAS were enrolled. We calculated the diagnostic accuracy of both the conventional (0.5 μg/ml) and age-adjusted (age × 0.01 in patients >50 years) D-dimer cut-offs. Result. D-dimer was higher in the AAS group (n = 82) than in the non-AAS group (n = 122) (10.85 (3.61–33.12) vs. 0.40 (0.23–1.07), OR: 1.139 (CI: 1.085 – 1.195), p<0.001). The D-dimer plasma level had an area under the ROC curve of 0.915 (CI: 0.873–0.956) with AAS. At the age-adjusted cutoff point compared to a 0.5 μg/ml cutoff, the sensitivity of 97.6% and the NLR of 0.04 did not change, but the specificity increased by 5.7% to 65.6%, the PPV increased by 3.6% to 65.6%, and the NPV slightly increased by 0.2% to 97.6%. Conclusion. Compared with a conventional method, the age-adjusted D-dimer cutoff may have higher specificity and PPV while maintaining high sensitivity for ruling out AAS.